[RETRACTED] Shaping Southeast Asian Taste: Curry as Historical Evidences of Muslim Trade Networks in the Indian Ocean - Bambang Widyonarko (Journal of Islamic History and Manuscript, 2023)
This article has been retracted following an action of violating against publication ethics. The Journal of Islamic History and Manuscript has just learned that the article has been proven to have plagiarized another article entitled "Curry: A Pleasant Memory of Spice Route" by Yuanita Wahyu Pratiwi. Following the guidelines set by the Publication Ethics Committee, the journal has determined that this may serve as grounds for retraction. The Journal of Islamic History and Manuscript regrets this academic error and apologizes to the readers and original authors who were harmed.